Whistleblowing Testing for Perceived Organizational Support as a Moderating Variable: Applying the Theory of Planned Behavior - Hadiyati, Siti Nur; Suhardjanto, Djoko; Rosnidah, Ida; Winarna, Jaka (Journal of Ecohumanism, 2024)
This study aims to examine the relationship between attitude, subjective norm, and perceived behavioral control with internal and external whistleblowing. It also evaluates the role of perceived organizational support (POS) as the moderating variable. This study adopts Ajzen's Theory of Planned Behavior (TPB), incorporating attitudes, subjective norms, and perceived behavioral control as key determinants of whistleblowing intentions, further exploring the moderating role of perceived organizational support in shaping the relationships between these TPB components and internal and external whistleblowing intentions. This study employs a survey questionnaire, and data collected from employees of banking company located in four cities in west java Indonesia. The warp partial least squares structural equation modeling (PLS-SEM) approach was employed to analyze the data and test the proposed model. The findings demonstrate that: (1) attitude and perceived behavioral control effect internal whistleblowing intention; (2) subjective norm effect both of whistleblowing intention channels. (3) POS is only able to moderate the influence of attitude on external whistleblowing intention. This study expands the existing literature by examining the role of perceived organizational support (POS) as a moderating variable between attitude, subjective norm, perceived behavioral control and both of whistleblowing intentions (internal & external). The originality and value of being a whistleblower lies in an employee's sense of belonging to their organization. It is crucial for organizations to establish a supportive and effective whistleblowing system to protect whistleblowers and prevent fraud. Future research should focus on comparing and analyzing employees from diverse backgrounds in Indonesia, and also consider enhancing the model with various moderating variables.